Specificity of Medical Care Provided in Case of Poisoning - Gafurov Abduvoid Khuseinovich; Azimov Ilyosbek Qahramon o’g’li; Egamberdiyev Jasurbek Jumanazar o’g’li; Usmonov Odiljon Sidiqovich (Zien Journals, 2022)
this thesis presents the problems associated with the provision of medical care to victims under the influence of highly effective toxic substances, their effect on the human body, methods of protection of the population in emergency situations associated with them, as well as recommendations for their elimination.
Keywords: strong-acting toxic substance; victim; First Aid; security